2004
DOI: 10.1038/sj.ijo.0802794
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxides in obese patients and effects of weight loss with orlistat on lipid peroxides levels

Abstract: OBJECTIVE: Obesity is a well-known risk factor of atherosclerosis. Recent studies showed that obesity is associated with enhanced lipid peroxidation. The aim of this study is to investigate the effect of weight reduction with orlistat treatment on lipid peroxidation levels. We assessed lipid peroxidation by measuring the concentration of plasma malondialdehyde (MDA). DESIGN: A randomized, controlled, open-label 6-month study. SUBJECTS: In total, 36 obese (body mass index (BMI) 430 kg/m 2 ) and 11 healthy age-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 27 publications
9
49
1
Order By: Relevance
“…Previous studies have shown that circulating MDA levels are higher in diabetic and obese subjects than in non-obese healthy controls (Prazny, Skrha, & Hilgertova, 1999). A reduction of fasting blood glucose levels as well as MDA levels have been previously reported to accompany weight loss in obese subjects (Yesilbursa, Serdar, Sarac, & Jale, 2005). The decrease in plasma MDA concentration observed in the current trial suggests that the whole process of lipid peroxidation was diminished by regular consumption of DG.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have shown that circulating MDA levels are higher in diabetic and obese subjects than in non-obese healthy controls (Prazny, Skrha, & Hilgertova, 1999). A reduction of fasting blood glucose levels as well as MDA levels have been previously reported to accompany weight loss in obese subjects (Yesilbursa, Serdar, Sarac, & Jale, 2005). The decrease in plasma MDA concentration observed in the current trial suggests that the whole process of lipid peroxidation was diminished by regular consumption of DG.…”
Section: Discussionsupporting
confidence: 62%
“…26 However, the risk appeared to decline after bariatric surgery, since LPO in the post-surgical obese group was lower than in the pre-surgical obese group. This result may be explained by the decline in body weight presented by the patients since, according to Yesilbursa,27 weight loss is accompanied by reduced ROS production and decreased MDA levels. These findings corroborate the study by Valezi et al, 28 who assessed oxidative stress indicators in obese patients before and after Roux-en-Y gastric bypass.…”
Section: Figurementioning
confidence: 97%
“…The effects of Orlistat treatment on lipid peroxide levels were examined in a sample of nondiabetic obese men and women. 46 All subjects took 120 mg of Orlistat three times daily; no other lifestyle changes were implemented. After 6 months of treatment, the mean body weight of the obese group was reduced from 91.579.…”
Section: Obesity and Evidence Of Oxidant Stress In Humansmentioning
confidence: 99%